Modelo de gestión inteligente en el fomento del turismo inclusivo en el destino Manta, Ecuador - Sánchez Zambrano, Oswaldo Ariel (2023)
The objective of this research was to design an intelligent management model to promote inclusive tourism in the Manta destination, Ecuador. It included a mixed approach of qualitative and quantitative interpretation of data, and based on the bibliographic documentation of García 2017 and Castro et al., 2019. Three phases were established for this study: starting with the situational diagnosis of inclusive tourism in the Manta destination, where the study area was characterized, the present accessibility was identified, the characteristics of the demand were determined and a SWOT/CAME analysis was carried out; the second phase was the selection and validation of the criteria for the Intelligent Management of Inclusive Tourism (GITI) under the assessment of experts who were professionals in topics of smart destinations and inclusive tourism. In the third phase, a proposal for the GITI was presented, outlining and developing the model. The findings demonstrated that the study area has potential in hotel infrastructure and tourist attractions, but presents significant deficiencies in terms of accessibility for tourists with disabilities. With the aim of addressing this lack and creating a management framework applicable in Manta city, a smart tourism management model has been developed. This proposal will contribute to Manta being a smart tourist destination that guarantees inclusive experiences for all visitors. The implementation of this model will be essential to fully exploit the region´s tourism potential and promote equal opportunities in tourism.